Rekomendasi Desain Dokumentasi Keperawatan untuk Praktik Keperawatan Mandiri - Hasti Primadilla; Fitarina Fitarina; Deni Metri (Jurnal Keperawatan Silampari, 2023)
This study aims to produce paper-based forms that meet the needs of nurses in home care. The method is development research referring to the concept of the Technology Acceptance Model. The results of the analysis show the nurse's belief in the form: believes and feels its usefulness, thinks and feels the ease of use, has a positive attitude towards the form as evidenced by the appreciation conveyed, socialization and advocacy plans to professional organizations, great interest in using it in practice and actual positive behavior demonstrated by multiplying the forms, applying them in practice and using them at the puskesmas home visits. Practitioners expect improvements in column size, increased nursing care content, and standardization. In conclusion, the forms produced in this study can be accepted by independent practice nurses, are ready to be applied, and can be adapted into electronic systems. Nurses have felt its usefulness and ease of use and have continuously proven its use in practice. Keywords: Documentation, Forms, Acceptance, Independent Nursing Practice